Peer-Assessment Academic Integrity Scale (PAAIS-24) - Jusuf Blegur; Herman Subarjah; Yusuf Hidayat; Amung Ma'amun; Agus Mahendra; I Made Sriundy Mahardika; Sefri Hardiansyah (Ital Publication, 2024)
This study aims to develop an academic integrity scale to help lecturers evaluate the academic integrity of university students with peer-assessment learning experiences using the ADDIE research and development method. Twenty-four items were designed using the concepts of academic integrity; honesty, trust, fairness, respect, responsibility, and courage validated by six raters and tested on 520 students from various universities in Indonesia. Testing content validity using the Aiken-V formula, construct validity testing using discriminant indexes, factor analysis (Exploratory and Confirmatory Factor Analysis), and concurrent validity testing by correlating PAAIS-24 with the developed Academic Integrity Scale. While the reliability test used Cronbach's alpha formula. The study results proved that each item of content validity meets with an Aiken value >0.80; on construct validity testing, the discriminant index value is >0.50, and the EFA and CFA loading factor values are >0.50. In addition, the model is appropriate because the theoretical model of PAAIS-24 is in accordance with empirical data. Whereas in reliability testing, Cronbach's alpha value is 0.95. Lastly, PAAIS-24 is one of the credible instruments. It contributes to developing knowledge that assists lecturers in measuring, assessing, and evaluating student academic integrity based on peer-assessment to promote increased academic performance. Doi: 10.28991/ESJ-2024-08-02-09 Full Text: PDF